Pengaruh Dukungan Orang Tua, Teman Sebaya dan Motivasi Belajar Terhadap Hasil Belajar Siswa Kelas XI IPS SMA PGRI 2 Kota Jambi - Redi Indra Yudha (Universitas Mathla'ul Anwar Banten, 2020)
The purpose of this study was to determine the effect of parent support, peers and motivation to learn the results of student learning class XI IPS in SMA PGRI 2 Kota Jambi. The population in the study amounted to 61 students. Based on the results of the study, it can be concluded that in taking the learning process of parent support is very necessary for the growth of children in further education, this is due to the desire of children to attend school is not limited to different school environments or new peers but there is a high desire to continue take knowledge that is beneficial to them